Analyzing Student Satisfaction Toward the Integration of ChatGPT as a Digital Learning Resource - Prasetya, Raynaldi Nugraha; Budiman, Ridho Dedy Arief (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study aims to analyze students’ satisfaction with the integration of ChatGPT as a digital learning resource at SMP Harapan Ananda, West Kalimantan. A descriptive quantitative approach was employed, involving 80 respondents from grades VII–IX who had used ChatGPT in their learning activities. Data were collected through a five-point Likert scale questionnaire, complemented by semi-structured interviews to strengthen the quantitative findings. Descriptive analysis revealed that students’ satisfaction was in the “satisfied” category, with an overall mean score of 4.13. The Ease of Use dimension obtained the highest score (4.35), followed by User Experience (4.25) and Learning Usefulness (4.10). Meanwhile, Information Reliability received the lowest score (3.82), indicating the need for teacher guidance in verifying the accuracy of ChatGPT-generated information. The results confirm that ChatGPT holds significant potential as a digital learning resource that enhances students’ motivation and learning autonomy, though its effectiveness still relies on active teacher involvement. This study contributes theoretically to technology acceptance research in education and provides practical implications for schools in designing ethical and contextually relevant AI-based learning strategies.